Implementation of Fuzzy Multi-Objective Optimization On The Basic Of Ratio Analysis (Fuzzy-MOORA) In Determining The Eligibility Of Employee Salary - I Gede Iwan Sudipa; I Nyoman Tri Anindia Putra; Dwi Putra Asana; Revan Dwi Hanza (Jurusan Teknik Informatika, 2021)
Purpose: CV. Harmoni Permata has several employees, and each employee has a bonus salary. However, in determining who is eligible for the employee salary bonus at CV. Harmoni Permata is still done manually assessment. This causes an error in the calculation because the decision-maker must look at previous historical data to decide.Design/methodology/approach: System design includes systems that can manage user data, position data, criteria data, criteria description data, absences data, task data, and assessment data, which will produce an assessment report. The MOORA method approach is used because it has calculations with minimum and simple math and has a good level of selectivity. Findings/result: The normalization comparison test of the manual calculation of the MOORA method with the system calculation results is the same, with the best five alternative employees who deserve a salary bonus.Originality/value/state of the art: Based on previous research reviews, this study uses the criteria for performance, honesty, attendance, and accuracy by determining the weight based on the type of benefit or cost and the MOORA method in calculating the final value of alternative ranking.